Isolation and characterization of Bordetella avium phase variants. - Gentry-Weeks, C R (1991)
Two spontaneous phase variants of Bordetella avium were isolated at a frequency of 2 x 10(-4) by colony immunoblot assay of B. avium with antibody against B. avium dermonecrotic toxin. The two phase variants, designated GOBL309 and GOBL312, lack dermonecrotic toxin and four outer membrane proteins with molecular masses of 93, 48, 38, and 27 kDa but retain the ability to agglutinate guinea pig erythrocytes. The proteins which are not expressed by GOBL309 and GOBL312 correspond to five proteins which are phenotypically modulated in B. avium by growth in the presence of nicotinic acid or MgSO4. Growth of the phase variants in supplemented Stainer-Scholte media containing nicotinamide did not alter expression of these five proteins. Intranasal inoculation of the spontaneous phase variants into 3-day-old turkeys and reisolation of B. avium at 2 weeks postinoculation resulted in the recovery of B. avium which had the wild-type phenotype, colonized the turkey tracheas, and produced the four outer membrane proteins and dermonecrotic toxin. Hybridization of B. avium and B. avium-like chromosomal DNA with internal portions of the Bordetella pertussis virulence regulatory genes, bvgA and bvgS, revealed that B. avium and B. avium-like isolates contain 5.3- and 5.7-kb DNA fragments, respectively, which are homologous to bvgS. B. avium and B. avium-like chromosomal DNA failed to hybridize to B. pertussis bvgA.